Pre-clinical and clinical evaluation of the malaria vaccines RH5-VLP and PfSPZ vaccine - Ishizuka, A (2016)
Despite progress through expanded use of bed nets and anti-malarial drugs, Plasmodium falciparum (Pf) malaria caused about 200 million cases and 500,000 deaths in 2015. An ideal vaccine would reduce the burden of disease and interrupt transmission. Despite decades of effort, there is no vaccine that can adequately address the global burden of malaria. This thesis focuses on two potential weaknesses in the parasite life-cycle. First, I investigate two vaccination strategies aimed at improving the antibody response to RH5, an essential and conserved protein for erythrocyte invasion. Due to instability of the resultant recombinant vaccine constructs, these efforts have required re-engineering of the vaccine platform, which remains an ongoing effort. Second, the immunogenicity and mechanism of protection of a live-attenuated whole sporozoite vaccine, PfSPZ Vaccine, was assessed. In a study that examined PfSPZ Vaccine at intravenous (IV) doses between 1.35 &tiles; 105 to 4.5 &tiles; 105 PfSPZ, I demonstrate that PfSPZ antibody responses correlated with durable sterile protection against controlled human malaria infection (CHMI). Surprisingly, the pre-vaccine frequency of Vγ9+Vδ2+ T cells, an innate T cell that recognizes conserved Plasmodium phosphoantigens, also correlated with durable sterile protection. Regarding the mechanism of protection, PfSPZ-specific antibodies as well as CD8 and CD4 T cells in the blood decreased substantially over time, yet sterile protection was maintained. In non-human primates, the CD8 T cell response in the liver at a memory time point was measured to be about 100-fold higher than found in the blood. Collectively, these data suggest that PfSPZ Vaccine confers durable protection in humans by long-lived, tissue-resident CD8 T cells. These findings were extended with a study using 9.0 x 105 PfSPZ, wherein I demonstrate that T cell responses peaked immediately after the first vaccination with minimal T cell activation despite additional immunizations. This suggests that anti-PfSPZ immunity may be limiting the effectiveness of subsequent immunizations. Finally, I examined the T cell response to PfSPZ attenuated by chloroquine (termed PfSPZ-CVac). T cell responses were substantially higher than achieved with comparable PfSPZ Vaccine doses. Additionally, a significantly higher proportion of PfSPZ-specific CD4 T cells were polyfunctional, simultaneously expressing IFN-γ, IL-2, and TNF-α, in subjects that were protected from CHMI. In sum, these studies provide insight into the immunobiology of a protective immune response that may guide future malaria vaccine development efforts.